Structure-property of thermoplastic polyurethane-clay nanocomposite based on covalent and dual-modified laponite - Mishra, Ananta K.; Rajamohanan, P. R.; Nando, Golok B.; Chattopadhyay, Santanu (Journal of Computational and Theoretical Nanoscience, 2011)
Modification of surface of clay platelets by ionic and covalent modification techniques renders it to be easily dispersed in polymers like, Thermoplastic Polyurethane (TPU). Only ionic or covalent modification techniques in isolation are not sufficient to achieve uniform nanoscale dispersion of Laponite (synthetic hectorite nanoclay) in TPU. Hence, the dual modification of Laponite (both ionic and covalent) is performed and the effects of the modification on the morphology, thermal and rheological behaviors of the TPU-modified clay nanocomposites have been studied. The degree of exfoliation of clay platelet in TPU matrix is found to be higher for dual functionalized nanoclays compared to their singly modified counterparts. Interestingly, dual modified Laponite clays prepared by using two different techniques (ionic followed by covalent and covalent followed by ionic) exhibit different morphology and properties. The dual modified clays significantly alter the equilibrium morphology of TPU. The storage modulus of the dual modified Laponite-TPU nanocomposite in the glassy region (at -60 degrees C) land in the rubbery region (+98 degrees C) is improved by 172.8% and 85%, respectively as compared to the neat TPU. Similarly, the onset of degradation is found to be enhanced by 28.7 degrees C as compared to the neat TPU.
Keywords: Dual modification; Laponite Nanocomposite; Morphology; Structure-Property; Thermoplastic polyurethane